Evaluating Corporate Social Responsibility (CSR) Program through the Social Return on Investment (SROI) Approach: A Case Study of Sundung Cisarua Program at PT ANTAM Gold Mining Business Unit - Arif Rahman Saleh; Edy Ayuba; Nabilla Dea Lukita; Yudianto (Global Writing Academica Researching and Publishing, 2025)
This study aims to analyze the success of the CSR program facilitated by PT ANTAM Gold Mining Business Unit, namely the Sistem Pengembangan Usaha dan Perlindungan Lingkungan Cisarua (Sundung Cisarua) Program, using the Social Return on Investment (SROI) approach. This research used a descriptive qualitative approach to evaluate the extent to which the program has a real impact on the community. The analysis results indicate that the program generates an SROI ratio of 5.45, meaning that every IDR 1 invested yields a social return of IDR 5.45. This achievement reflects that the Sundung Cisarua Program provides significant social benefits and also has a positive impact on economic and environmental aspects. Therefore, the program is considered effective and feasible for further development and replication in other areas with similar characteristics.